Pengaruh Service Recovery terhadap Customer Satisfaction Penumpang Maskapai Penerbangan Internasional di Indonesia - Devi Destiani Andilas; Albertus Raymond Gunardi; Michael Christopher Elim (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2021)
This research intend to analyze the effect of service recovery (atonement, tangible, empowerment, communication, explanation, feedback) on customer satisfaction, especially for international airline passenger in Indonesia. Data were collected via an online survey of International Airlines Passenger who had ecperienced service failure. In total, 70 respons were used for final anlysis. Multiple linear regression was used to analyse the proposed hypotheses. The result shows that just atonement, communication, and empowerment has significantly influence customer service recovery satisfaction.